Solubility and thermodynamic properties of sulfuryl fluoride in water. (April 2016) - Liang, Xiaojiang; Nie, Yong; Deng, Dongshun; Lu, Meizhen; Yu, Fengwen; Chen, Ping; Ji, Jianbing
Highlights: More solubility data of SO2 F2 in water were provided for theoretical study. Henry's law constants of SO2 F2 in water were determined. The thermodynamic properties of SO2 F2 dissolution in water were obtained. Abstract: The solubility of sulfuryl fluoride in water was experimentally measured over the pressure from P  = (0 to 600) kPa and T  = (283.15 to 308.15) K using isochoric saturation method. Results show that SO2 F2 solubility increases with increasing pressure and decreases with increasing temperature. Using the experimental solubility data, Henry's law constants and the thermodynamic properties such as the standard Gibbs free energy, enthalpy, and entropy changes of SO2 F2 solvation were obtained. Henry's law constant based on mole fraction and molality of SO2 F2 in water vary from (432.21 to 1052.96) MPa and (7.78 to 18.96) MPa at T  = (283.15 to 308.15) K, respectively.